The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.14742/ajet.3240
|View full text |Cite
|
Sign up to set email alerts
|

Factors influencing peer learning and performance in MOOC asynchronous online discussion forum

Abstract: Most studies on traditional asynchronous online discussion suggest that facilitating dialogue, that is, commenting forum activities, result in better learning and performance. However, due to open entry and diverse learner backgrounds, learner behaviour in massive open online courses (MOOCs) may be different. Viewing forum messages, which involves fewer mental and physical actions as well as less cognitive processing, rather than posting forum massages, might better match the learner's study purpose. In this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
82
0
3

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 142 publications
(89 citation statements)
references
References 41 publications
4
82
0
3
Order By: Relevance
“…In conventional online courses, learners usually share the same academic goals, are familiar with one another, and are supervised closely by the teacher (Chiu & Hew, 2018). However in MOOCs, learners do not know most of their peers, are not supervised by the teacher, and are under no expectation to complete the course (Chiu & Hew, 2018).…”
Section: Figure 1 Growth Of Moocs As Presented Bymentioning
confidence: 99%
“…In conventional online courses, learners usually share the same academic goals, are familiar with one another, and are supervised closely by the teacher (Chiu & Hew, 2018). However in MOOCs, learners do not know most of their peers, are not supervised by the teacher, and are under no expectation to complete the course (Chiu & Hew, 2018).…”
Section: Figure 1 Growth Of Moocs As Presented Bymentioning
confidence: 99%
“…Forum discussion is one of the main features and activities within MOOC structure apart from content delivery, assessment and evaluation. The forum discussion activities described as viewing, voting and commenting [1]. Johnson [6] has explained in a general perspective on the challenges of the virtual learning environment, which is relatable to the MOOC current environment as listed below.…”
Section: A Research Backgroundmentioning
confidence: 99%
“…Each learns within personal pace, then required completing the quiz, practical exercise and peerreviewed project. In general, learning activities in MOOC can be classified into two categories: receiving information (e.g., video lectures), and peers or instructors interaction (e.g., forum discussion) [1].…”
Section: Introductionmentioning
confidence: 99%
“…Wise and Cui (2018) found that students who contributed to forums had higher passing rates than those who did not, although among the learners who passed the course there were no differences in course grades between contributors and noncontributors to the forums. Chiu and Hew (2018) found that it was actually the viewing of the messages rather than posting contributions to the forums that increased quiz scores. Onah, Sinclair and Boyatt (2015) compared tutor supported and peer supported forums, and found higher completion rates among students who chose the tutor supported mode.…”
Section: Literature Reviewmentioning
confidence: 99%